Perbandingan Mixing Foundation dengan Teknik Bakar dan Tanpa Teknik Bakar Terhadap Kulit Wajah Berminyak dalam Ketahanan Riasan Wajah Pengantin Sumatera Barat - Amelia Hanif; Indah Permata Sari; Siska Miga Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Everyone wants to have an attractive and beautiful appearance, especially women. Beauty is a necessity for women because it can support everyone's self-confidence. Basically, beauty is sufficient, everyone has their own perception of true beauty. Efforts to reflect one's beauty can be done with cosmetics, both care cosmetics and decorative cosmetics. For some people, cosmetic care means efforts to care for facial skin, so that skin is healthy and bright through the use of facial soap, moisturizer, and serum and vitamins for the face. This type of research is a type of experimental research. Data collection techniques in this research include observation and documentation using the burn technique (X1) for oily facial skin. The results were compared with the application of mixing foundation without the burn technique (X2) and this was also reinforced using comments. the average panelist ratings are not aligned in the two groups. When applying mixing foundation using the X1 burn technique for oily skin, the average score for the resistance indicator was 100% in the long-lasting category, the smoothness indicator obtained an average of 85% in the smooth category and the panelists' favorite indicator obtained an average of 85% like category